Interleukin-16 rs4072111 Polymorphism is Associated with the Risk of Peri-Implantitis in the Chinese Population - Chen Z; Chen G (Dove Medical Press, 2021)
Zongfei Chen,1 Guanhua Chen2 1Fujian Key Laboratory of Oral Diseases & Fujian Provincial Engineering Research Center of Oral Biomaterial & Stomatological Key Laboratory of Fujian College and University, School and Hospital of Stomatology, Fujian Medical University, Fuzhou, Fujian, People's Republic of China; 2Institute of Stomatology & Research Center of Dental and Craniofacial Implants, School and Hospital of Stomatology, Fujian Medical University, Fuzhou, Fujian, People's Republic of ChinaCorrespondence: Zongfei ChenFujian Key Laboratory of Oral Diseases & Fujian Provincial Engineering Research Center of Oral Biomaterial & Stomatological Key Laboratory of Fujian College and University, School and Hospital of Stomatology, Fujian Medical University, 246 Yangqiao Zhong Road, Fuzhou, Fujian, 350002, People's Republic of ChinaTel/Fax +86-0591-83700838Email zongfei@fjmu.edu.cnPurpose: Peri-implantitis (PI) is a major contributor to dental implant failure. Genetic predisposition plays an essential role in the development of PI. The purpose of this study was to investigate the correlation of IL-16 gene single nucleotide polymorphisms (SNPs), rs11556218 and rs4072111, with PI at the gene level.Patients and Methods: A total of 162 patients with PI and 162 cases with healthy implants were recruited as the case and control groups, respectively. The genotypes were analysed using direct sequencing. The genotype and allele proportion between the case and control groups were compared using the chi-square test. The periodontal status of patients carrying different genotypes was analysed, including gingival index, plaque index, calculus index, peri-implant pocket depth (PPD), and clinical attachment level (CAL).Results: The case and control groups were age- and gender-matched. In the case group, the rs4072111 CT genotype was majorly observed, and the T allele carriers showed a high PI risk. Patients with the rs4072111 CT genotype had worse periodontal status, which was reflected by the higher levels of the gingival index, plaque index, calculus index, PPD and CAL. The distribution of the rs11556218 genotype and T allele showed no significant difference between the case and control groups (P > 0.05).Conclusion: The CT genotype of IL-16 gene rs4072111 SNP can be used as a factor assessing PI risk. Therefore, IL-16 genetic variation may be related to PI susceptibility in the Chinese Han population.Keywords: peri-implantitis, IL-16, rs4072111, rs11556218, susceptibility